Cover Feature: Polymers Based on Cyclic Carbonates as Trait d'Union Between Polymer Chemistry and Sustainable CO2 Utilization (ChemSusChem 4/2019). Issue 4 (15th February 2019) - Yadav, Neha; Seidi, Farzad; Crespy, Daniel; D'Elia, Valerio
Abstract : The Cover Feature shows five‐membered cyclic organic carbonate monomers strategically placed at the heart of a process that combines renewable, naturally available building blocks with abundantly available waste CO2 for the synthesis of polymers. In this way, cyclic carbonates play a pivotal role in connecting sustainable chemistry with the synthesis of everyday‐life materials represented by foams, adhesives and components of lithium batteries". More information can be found in the Review by Neha Yadav et al. onpage 724 in Issue 4, 2019 (DOI:10.1002/cssc.201802770 ).